The Sustainable Composite Materials in Civil and Architectural Engineering - Li, Yeou-Fong; Chen, Walter; Cheng, Ta-Wui (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is a collection of 10 research articles (from 18 submissions) authored by researchers and peer reviewed by professionals in the field to address the use of sustainable composite materials in civil and architectural engineering over the course of more than 2 years. Fiber-reinforced plastic (FRP), geopolymers, and various recycled and repurposed waste materials are among the items addressed, used in a variety of applications from flame retardance to energy consumption. This book is a great resource for both academics and professionals in the field of engineering.